KARAKTERISTIK PEMASANGAN HAK TANGGUNGAN TERHADAP HARTA PERKAWINAN - Danarta, Kadek Setyawan (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
In essence the law is the realization of the protection of the interests of the community. Regarding Marriage Assets Law between husband and wife regulated in the Marriage Law has different legal principles from the Civil Code, so that in its application, Marriage Assets Law is subject to two legal systems, namely Marriage Assets Law based on Civil Code and Wealth Law Marriage based on the Marriage Law. The purpose of this thesis article is about the problem, the legal position of marital property in a household if it is used as a mortgage and the implementation of the mortgage rights to the marriage assets. In this article research uses a normative juridical method with an empirical juridical approach to refer to Law No. 1 of 1974 concerning Marriage. The results of the study basically if there is a marriage there will be a mixture of wealth between husband and wife, if the marriage is not accompanied by a marriage agreement, between the two parties there will be a round of wealth. (1) The legal status of marital property in a household if it is made a mortgage or legal property of marriage in jurisprudence has been accepted by the principle of transitory law. (2) Then the implementation of the installation of mortgages to marital assets must always be approved by both parties both husband and wife. While the granting of mortgages is preceded by a promise to provide mortgages as collateral for repayment of certain debt, which is stated in and is an integral part of the debt agreement.